(untitled) (Research, Society and Development, 2023)
Introduction: The end of 2019 and the beginning of 2020 is marked by one of the biggest challenges to health systems in the 20th century. After the outbreak of the pandemic caused by the new coronavirus, children were subjected to social isolation. Therefore, regarding the lifestyle of preschoolers and schoolchildren, a factor that drew attention was the influence of the intensification of screen exposure and its possible influence on the quality of sleep. Objective: The objective was to evaluate the impact of electronic device screens on children’s sleep quality in times of the COVID-19 pandemic in the city of Aracaju. Methods: Questionnaires were applied via electronic form, after collection, the categorical variables of interest were crossed with the children’s screen time during the pandemic carried out in Aracaju, carried out using the Chi-square test (c2). Results: The data found demonstrate that early and extensive exposure to screens is associated with unsatisfactory sleep, in relation to the short duration of sleep, as well as its efficiency. Conclusion: Based on the information obtained, it is possible to conclude in this study that the COVID-19 pandemic has significantly impacted children’s routine, including the abuse of electronic device screens in the child population, which brings numerous harms, including the quality of sleep.